Outdoor ground surface influences spatiotemporal parameters of walking for individuals undergoing rehabilitation: An observational study - Benjamin S. Killen; Stacy Harris; Alan Levinson; Catherine Hamilton; Michael D. Lewek (PLoS ONE, 2025)
Clinical measures of walking capacity may differ from walking performed in outdoor environmental settings. This study assessed spatiotemporal aspects of gait in individuals undergoing rehabilitation when walking over various outdoor surfaces and compared them to a standard clinical gait measure. We sought to identify how spatiotemporal aspects of gait change across terrains commonly encountered in the community in individuals undergoing rehabilitation. Forty-six individuals with mobility deficits undergoing outpatient physical therapy completed the 10-meter walk test in clinic and walked over six standardized terrains (e.g., pavers, gravel, sand). We calculated gait speed, cadence, average step length, and walk ratio (calculated as cm/steps/min) from video recordings for all conditions and used repeated measures ANOVAs to assess differences between terrains compared to the 10-meter walk test. We then used multiple linear regressions to examine spatiotemporal mechanisms underlying gait speed changes across terrains. Gait speed and cadence were reduced when participants walked over sand, mulch, up sloping gravel, and down sloping gravel compared to the 10-meter walk test. Step length decreased in the sand, gravel upslope, and gravel downslope conditions compared to the 10-meter walk test. Walk ratio was decreased in the sloped gravel conditions. Cadence and step length changes explained 95–99% of the variance in gait speed changes across conditions with step length being more heavily weighted across conditions. Individuals undergoing physical therapy for mobility deficits walked slower, with smaller step lengths and cadence when faced with uneven outdoor terrain compared to an indoor 10-meter walk test while walk ratio remained consistent across level surfaces. Speed reductions were related to both step length and cadence. Walk ratio remained consistent across level terrains, indicating a consistent central control strategy, despite terrain changes. Although standardized measures like the 10-meter walk test provide critical information about gait capacity, they may not fully reflect performance in all real-world environments.